2013
DOI: 10.1007/s10841-013-9547-y
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetle assemblage structure across the aridity and trophic resource gradient of the Botswana Kalahari: patterns and drivers at regional and local scales

Abstract: Understanding pattern and process at both regional and local scales is important for conservation planning although such knowledge of insects is frequently lacking. To assess patterns along a regional gradient of increasing aridity and diminishing food resources in the Botswana Kalahari, Scarabaeine dung beetles were sampled quantitatively using four dung types at three local sites in six regional areas. At regional scale, factor analysis of species abundance extracted a maximum of six factors, each dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 36 publications
(39 reference statements)
1
39
0
Order By: Relevance
“…2), two were represented across the gradsect, aeolian sands at Chobe in the northeast and at Khutse, Mabuasehube, and Transfrontier in the southwest, with fossil lacustrine deposits in the intervening Mababe (Savuti) and Makgadikgadi Depressions (North CKGR) in the northeast. However, analysis of soil texture at each of 18 study sites showed no significant differences between landscape types as each comprised predominantly sand (adjusted figures: 97.1% -99.6% sand) (Tshikae et al 2012a). …”
Section: Study Region and Geographical Gradientsmentioning
confidence: 84%
See 4 more Smart Citations
“…2), two were represented across the gradsect, aeolian sands at Chobe in the northeast and at Khutse, Mabuasehube, and Transfrontier in the southwest, with fossil lacustrine deposits in the intervening Mababe (Savuti) and Makgadikgadi Depressions (North CKGR) in the northeast. However, analysis of soil texture at each of 18 study sites showed no significant differences between landscape types as each comprised predominantly sand (adjusted figures: 97.1% -99.6% sand) (Tshikae et al 2012a). …”
Section: Study Region and Geographical Gradientsmentioning
confidence: 84%
“…The two regional components are correlated most strongly to annual rainfall, temperature during sampling, and an index derived from the density of 25 mammal species across the gradient (Tshikae et al 2012a). One southwest-centred regional component declined in proportional contribution to the northeast whereas the other component was centred in the northeast and declined to the southwest.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations